SOSIALISASI OPTIMALISASI PERSONAL BRANDING STRATEGI EFEKTIF MEMANFAATKAN MEDIA SOSIAL UNTUK SUKSES PRIBADI DAN PROFESIONAL DI SMA KI HAJAR DEWANTORO KOTA TANGERANG - Yeskarwani Gulo; Fitri Nurlaela; Badriah Nursakinah (Abdi Jurnal Publikasi, 2025)
This study aims to socialize and optimize the use of social media in order to build effective personal branding among students of SMA KH Dewantoro, Tangerang City. In today's digital era, social media has a very important role in shaping self-image and introducing individual potential to the public. Therefore, it is important for students to understand the right strategy in utilizing social media in order to support their personal and professional success in the future. Through this socialization, it is hoped that students can be wiser in using social media for productive and positive purposes. In this socialization activity, an understanding of the concept of personal branding is given, namely an effort to build a strong and consistent self-image in cyberspace. Students are taught how to choose the right social media platform, manage content that is in accordance with personal values, and maintain ethics and professionalism in interacting in the digital world. In addition, students are also given practical training on how to optimize their social media accounts to support career development and build useful professional networks. The results of this socialization activity show that the understanding of the importance of personal branding among students has increased significantly. They began to realize how big the impact of social media is on achieving personal and professional goals. With the right strategy, students can use social media effectively to improve communication skills, expand relationships, and open up career opportunities in the future. This socialization also succeeded in educating students on how to maintain a positive image in cyberspace, which in turn can help them achieve success in the professional world.